Governance and Urban Service Delivery in Zimbabwe (The Strategic Review for Southern Africa, 2020)
It is contended that service delivery is the core function of developmental local government. The provision of services such as waste management, water and health services is closely associated with the well-being of urban dwellers. In the period leading to the adoption of Zimbabwe’s 2013 Constitution, many people supported the devolution of services and functions to local government. It was a major victory when local government was elevated and given constitutional protection. There was great expectation that service delivery would improve in the cities, towns and smaller urban centres. Seven years later, that expectation appears not to have been realised. Instead, indications are that urban service delivery is experiencing a downward spiral. Using open-ended questionnaires, closed-ended questionnaires and the focus group discussions research methods, the article investigates the drivers of inadequate service provision in four urban areas in Zimbabwe. The paper also proffers suggestions for improving service delivery. The results of the study underscore that the causes of insufficient service provision are multi-pronged and not necessarily limited to inefficiency and ineffectiveness on the part of urban councils. In fact, a major recurring finding is that national government policies are big factors contributing towards the decline of urban service delivery.
Keywords: Governance; Service delivery; Urban Councils; Zimbabwe; Service Consumers